2022
DOI: 10.1097/tp.0000000000004209
|View full text |Cite
|
Sign up to set email alerts
|

Recipient and Center Factors Associated With Immunosuppression Practice Beyond the First Year After Liver Transplantation and Impact on Outcomes

Abstract: Background. Immunosuppression is a critical aspect of post-transplant management, yet practices at intermediate and late time points after liver transplantation (LT) are poorly characterized. Methods. A retrospective cohort of 11 326 adult first LT alone recipients between 2007 and 2016 was identified by linking United Network for Organ Sharing transplant data to Medicare administrative claims. The immunosuppression regimen was obtained from Medicare billing claims. Factors associated with calcineurin inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Immunosuppressants, especially tacrolimus and sirolimus, are the critical maintenance agents of post-transplant management. 43 Although their effect on disrupting the homeostasis of hepatic glucose and lipid metabolism has been studied extensively, 44,45 there are limited experimental data about their effect on the connection between macrophages and hepatocyte metabolism. Previous studies have found that tacrolimus treatment could drive macrophages toward an anti-inflammatory phenotype and reduced their production of cytokines, such as CCL1, CXCL10, CXCL1, and TNF-α, 46,47 whereas sirolimus could promote the proinflammatory phenotype of macrophages by increasing expression of monocyte chemoattractant protein-1, TNF-α, and interleukin-1β.…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppressants, especially tacrolimus and sirolimus, are the critical maintenance agents of post-transplant management. 43 Although their effect on disrupting the homeostasis of hepatic glucose and lipid metabolism has been studied extensively, 44,45 there are limited experimental data about their effect on the connection between macrophages and hepatocyte metabolism. Previous studies have found that tacrolimus treatment could drive macrophages toward an anti-inflammatory phenotype and reduced their production of cytokines, such as CCL1, CXCL10, CXCL1, and TNF-α, 46,47 whereas sirolimus could promote the proinflammatory phenotype of macrophages by increasing expression of monocyte chemoattractant protein-1, TNF-α, and interleukin-1β.…”
Section: Discussionmentioning
confidence: 99%
“…This was a retrospective cohort study using a linked database created The data linkage process used for this study has been previously described. 13 The Health Resources and Services Administration, U.S. ents were excluded, due to inherent differences in immunosuppression practices and given the concern that they may be at higher baseline risk of OI, yet not representative of the vast majority of LT recipients. 15…”
Section: Data Source and Study Populationmentioning
confidence: 99%
“…Maintenance regimen at hospital discharge was categorized as: calcineurin inhibitor (CNI) with anti-metabolite (antiM) and steroid, CNI+antiM, CNI+steroid, CNI only, or other. Due to high rates of data missingness in the OPTN data beyond LT hospital discharge, Medicare claims data were used to capture immunosuppression practices thereafter 13. Prescription claims were sourced from prescription (Part D), outpatient, and durable medical equipment Medicare claims files.…”
mentioning
confidence: 99%